MODEL PENGURANGAN KADAR ALERGEN INHALAN DEBU RUMAH BERBASIS PENGELOLAAN DAN KARAKTERISTIK LINGKUNGAN INTERNAL RUMAH PADA PENDUDUK PERKOTAAN - Ainur Rofieq (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2014)
This studyis aimed at designing a model to reduce allergen inhalant level onhouse dust based on domestic environment management and characteristics in urban community. In this descriptive analytic study, houses whose occupants were infected by atopic respiratory diseases in Malang Regency were treated as the population. Using cluster random sampling, 40 houses from six urban districts were taken as the sample. Two types of variables were covered in this study; they were latent variables and latent sub-variables. The former consisted of eight domestic environment variables: education-economy, house dust management skill, house infrastructure, occupant characteristics, physical environment, chemical dust environment, biotic environment, and house dust allergen inhalant sources. Meanwhile, the latter covered all the variables treated as indicators in every latent variable.  This model of allergen inhalant reduction level is a structural model designed through multidimensional relationships among eight latent variables that have been theoretically and empirically developed. The relationship model between every latent variable and its indicator(s) was reflectively arranged. The structural model was analyzed using SmartPLS, a varian-based Structural Equational Modeling (SEM) approach. The procedures of the analysis were adapted from Wiyono’s (2011) and Jogiyanto’s (2009). The findings revealed that a significant structural model was achieved when the multidimensional relationships among the eight latent variables were directly and indirectly arranged. This significant structural model of allergen inhalant reduction level illustrated three hierarchical relationship levels. At the first level, the house dust allergen inhalant sources variable was only directly influencedby the biotic environment. The second level was maintained when the biotic environment variable was directly influenced by the physical and chemical environments, while the other four latent variables were indirectly influenced. At the third level, the house dust chemical variable was directly influenced by the house infrastructure and occupant characteristics, while the house dust management skill and education-economy variables were indirectly influenced. Keywords: house dust, allergen inhalant, urban community